Work Motivation Women Entrepreneurs in Islamic Economic Perspective: (Study at the Simpang Kandis, Sumber Jaya Village, Kampung Melayu District, Bengkulu City) - Cresy Lorenza; Romi Adetio Setiawan; Yenti Sumarni; Nilay Shah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
Population growth which continues to increase every year will cause many problems, one of which is the lack of job opportunities, as a result the number of unemployed is increasing which has an impact on economic conditions in Indonesia. Therefore, economic development will be more successful if it is supported by entrepreneurs who can create job opportunities. Entrepreneurship is not only dominated by men but also the emancipation of women. Women who choose to become entrepreneurs certainly have their own reasons why they made the decision to become entrepreneurs. This research aims to determine the background that motivates women to engage in entrepreneurial activities and to determine the Islamic economic perspective related to the work motivation of entrepreneurial women in the Simpang Kandis area, Sumber Jaya Village, Kampung Melayu District, Bengkulu City. This research uses a qualitative descriptive approach using field research. The research results show that women's work motivation in entrepreneurship in Simpang Kandis is caused by several factors, including economic needs, encouragement from the family, and available market potential. In an Islamic economic perspective, women are permitted to engage in entrepreneurship outside the home, but this must be accompanied by permission or blessing from their husband or parents. Apart from that, they are also expected not to neglect their household duties and become entrepreneurs with the aim of meeting their daily needs. However, this research also shows that women involved in entrepreneurship have not fully implemented the values recommended by Islam. Even though they have good intentions, piety in their work, and sincerity in their work, they are not yet fully transparent in selling their products to consumers regarding the quality of their merchandise. Apart from that, a friendly attitude towards buyers is also lacking. This research indicates that there is potential to increase the suitability of women's entrepreneurial practices with Islamic values in the Simpang Kandis area. However, further efforts are needed to improve the understanding and implementation of these values in their entrepreneurial practices.